Properties of AOT reverse micelle interfaces with different polar solvents - Luna, Maria Alejandra (2016)
The behavior of polar solvents such as formamide, ethylene glycol, propylene glycol, glycerol, dimethylformamide (DMF), and dimethylacetamide (DMA), entrapped in n-heptane/sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT) reverse micelles (RMs) was investigated using absorption, emission, and the red edge excitation shift technique. We use the solvatochromism behavior of the hemycianine 4-(4-[dimethylamino]-styryl)-1-methylpyridinium iodide (HC) to investigate the physicochemical properties such as micropolarity, microviscosity, and hydrogen bond (H-bond) interaction in the non-aqueous RMs. Our results demonstrate that AOT surfactant interacts through H-bond with formamide, ethylene glycol, propylene glycol, and glycerol,and this interaction is responsible for weakening the electrostatic interaction between HC-AOT when entrapped in n-heptane/AOT RMs in absence of a polar solvent. On the other hand, when non-H-bond donor solvents (DMF and DMA) are incorporated inside the RMs, the structure of both pure solvents is destroyed upon encapsulation by the Na+-DMF or Na+-DMA interaction at Ws (Ws = [polar organic solvent]/[AOT]) ≤1.5. Our results show how the physicochemical properties, such as micropolarity, microviscosity, and H-bond interaction, of non-aqueous n-heptane/AOT RMs interfaces can be dramatically changed by simply using different non-aqueous polar solvent. Thus, these results can be very useful for employing these RMs, stabilizing enzymes, and using them as nanoreactors. Copyright © 2016 John Wiley & Sons, Ltd.